(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
Bleeding tendency is the manifestation of a wide range of abnormalities that can basically classify into two major categories according to etiology; these are the inherited and acquired categories. The pathologic defect resides in one of the three major sequential physiologic processes of blood homeostasis. Defects in coagulation include mainly inherited defect in the synthesis of one of the members of factors of coagulation such as factor VIII (Hemophilia A) and factor IX (Hemophilia B) and to a much less extent factor XI (Hemophilia C). The current study aimed to explore the oral health status in a sample of hemophilia male children. The present case control study included 22 children with hemophilia disorders and 50 apparently healthy aged matched control children. The age of hemophilia children ranged from 2-14 years. Dmft and DMFT were assessed and the results showed that patients had significantly higher scores indicating poor oral hygiene. Conclusion: hemophilia is a predisposing factor for poor dental hygiene and that protective measures should be seriously considered in such population to avoid serious complication following invasive dental procedures.